Gambaran Subjective Well-Being pada Perempuan dengan Hypersexuality - Winata, Gabriella; Engry, Agustina (Universitas Ciputra Surabaya, 2025)
Hypersexuality can profoundly affect the subjective well-being of women, causing feelings of worthlessness, shame, disruptions in daily life. Despite this, hypersexuality can also have positive effects, such as relaxation and happiness. This research, employing phenomenological methods and in-depth interviews with two women (aged 25 and 26), explores the subjective well-being of women with hypersexuality. Findings indicate that these women experience various aspects of subjective well-being, though at low levels. Positive affect arises from emotional support from sexual partners and post-sexual activity calmness. However, negative affect includes feelings of worthlessness and shame towards future partners, hindering stable relationships. Compulsive thoughts and conflicts create a cyclical pattern impacting life satisfaction. Inconsistencies between moral beliefs and actions trigger cognitive dissonance, prompting moral disengagement to justify sexual behaviors. Unsupportive family conditions and the aftermath of sexual abuse worsen subjective well-being, while support from sexual partners enhances it.